2008
DOI: 10.1007/s11746-008-1257-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Methyl Linoleate in Oil‐in‐Water Micro‐ and Nanoemulsion Systems

Abstract: Oxidation of methyl linoleate in O/W emulsions having droplets of median diameters ranging from 17 nm to 8.0 lm was carried out at 40°C. The oxidation process was analyzed on the basis of a kinetic equation of the autocatalytic type. The induction period was found to be shorter and the oxidation rate constant lower for emulsions with smaller oil droplets. The stoichiometry between methyl linoleate and oxygen was observed to be independent of both the size of oil droplet and the type of the surfactant and was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 20 publications
2
27
0
1
Order By: Relevance
“…The stoichiometric coefficient could be approximated to be unity in the first half of the oxidation, but it remarkably increased in the latter half of the oxidation as the oxidation proceeded. The relationship for methyl linoleate in a bulk system at 40 17) is also shown in the figure and was the same as those for the encapsulated methyl linoleate. This fact indicated that encapsulation of methyl linoleate with maltodextrin did not affect its oxidation mechanism.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The stoichiometric coefficient could be approximated to be unity in the first half of the oxidation, but it remarkably increased in the latter half of the oxidation as the oxidation proceeded. The relationship for methyl linoleate in a bulk system at 40 17) is also shown in the figure and was the same as those for the encapsulated methyl linoleate. This fact indicated that encapsulation of methyl linoleate with maltodextrin did not affect its oxidation mechanism.…”
mentioning
confidence: 71%
“…This fact indicated that encapsulation of methyl linoleate with maltodextrin did not affect its oxidation mechanism. represents the oxidation of methyl linoleate in a bulk system at 40 17) .…”
mentioning
confidence: 99%
“…Several studies showed better oxidative stability for emulsions with a large droplet diameter. [39][40][41][42] These reports suggested a higher oxidation rate with a smaller interfacial area of the oil droplet. Conversely, some papers reported the opposite results.…”
Section: Stability Of Encapsulated Sq Powdersmentioning
confidence: 95%
“…Jacobsen et al (2001) similarly reported that in the initial stage of storage, an increase in the size of droplets was positively correlated with decreased oxidation rate in fish oil enriched mayonnaise. Other researchers claim that the emulsion droplet interfacial area has a minimal impact on the oxidation rates (Imai et al, 2008;Nakaya et al, 2005;Shimada, et al, 1992;Sun and Gunasekaran, 2009). …”
Section: (3) Effect Of Properties Of the Emulsion Droplets On Lipidmentioning
confidence: 99%